An evaluation of government‐recommended stocking systems for sustaining pastoral businesses and ecosystems of the Alpine Meadows of the Qinghai‐Tibetan Plateau. Issue 8 (2nd April 2018) - Wang, Yingxin; Hodgkinson, Kenneth C.; Hou, Fujiang; Wang, Zhaofeng; Chang, Shenghua
Abstract: China introduced the "Retire Livestock and Restore Grassland" policy in 2003. It was strengthened in 2011 by additional funding for on‐farm structures. On the Qinghai‐Tibetan Plateau (QTP), fences were erected, livestock excluded from degraded areas, rotational stocking introduced, nighttime shelters were built, forages grown, and seed sown. However, the effectiveness of these actions and their value to Tibetan herders has been questioned. We conducted a sheep stocking experiment for 5 years in an Alpine Meadow region of the QTP to evaluate stocking options recommended by Government. Cold and warm season stocking each at three rates (0, 8, and 16 sheep/ha) and continuous stocking at 0 and 4 sheep/ha were compared. We measured live weights of sheep, plant species richness and evenness, root biomass and carbon (C), nitrogen (N) and phosphorus (P) contents of the 0–10 cm of soil. We found that resting grassland from stocking during the warm season for later cold season stocking significantly reduced plant species richness and evenness and root biomass but not soil C, N, and P. During cold season stocking, live weights of sheep declined whether at a stocking rate of 8 or 16 per ha. In contrast, sheep continuously stocked on grassland at 4 per ha gained weight throughout both the warm and cold seasons and plant species richness and evenness were maintained. Warm season stocking at 8 and 16 sheep/ha increased plant species richness and root biomass but reduced plant species evenness. Resting these alpine grasslands from stocking in the warm season has adverse consequences for plant conservation. Fencing from stocking in the warm season is not justified by this study; all grassland should be judiciously stocked during the warm season to maintain plant species richness. Neither resting nor stocking during the cold season appears to have any adverse consequences but sheltering and in‐door feeding of sheep during the cold season may be more profitable than cold season stocking with use of open nighttime yards. Abstract : We conducted a sheep stocking experiment on the Qinghai‐Tibetan Plateau to evaluate stocking options. Cold and warm season stocking each at three rates (0, 8, and 16 sheep/ha) and continuous stocking at 0 and 4 sheep/ha were compared. We measured changes in live weights of sheep, plant species richness and evenness, root biomass and carbon (C), nitrogen (N), and phosphorus (P) contents of the 0‐ to 10‐cm soil. We found that resting from grazing during the warm season for cold season stocking significantly reduced plant species richness and evenness and root biomass but not soil C, N, and P. Also during the cold season, the live weights of the sheep declined whether at a stocking rate of 8 or 16 per ha. In contrast, sheep continuously stocked on grassland at 4 per ha gained weight throughout both the warm and cold seasons and plant species richness and evenness were maintained. Warm season stocking at 8 and 16 sheep/ha increased plant species richness and root biomass but reduced plant species evenness. Resting these alpine grasslands from stocking in the warm season has adverse consequences for plant conservation. Therefore, the maintenance of different areas for warm season and cold season stocking is not justified by this study.